1986
DOI: 10.1002/tera.1420340304
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects on the CD‐1 mouse embryo exposed to concurrent doses of ethanol and aspirin

Abstract: Human fetal alcohol syndrome characteristics have been seen in the mouse fetus by several investigators who dosed the dam with only one or two doses of alcohol. The purpose of this study was to determine if the fetal effects of acute doses of alcohol (ethanol) are altered by aspirin. CD-1 mice were given two IP doses of a 25% v/v solution of 95% ethanol/saline (2.5 hours apart) and intubated with 250 mg/kg aspirin. The treatment regimen, begun at 8 days, 4 hours gestation, consisted of either aspirin pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Unfortunately, salicylic acid alone can be teratogenic (Joschko et al. 1993; Padmanabhan and Pallot 1995), and together ethanol and salicylic acid compromise fetal size and viability (Guy and Sucheston 1986; Padmanabhan et al. 1994; Padmanabhan and Pallot 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, salicylic acid alone can be teratogenic (Joschko et al. 1993; Padmanabhan and Pallot 1995), and together ethanol and salicylic acid compromise fetal size and viability (Guy and Sucheston 1986; Padmanabhan et al. 1994; Padmanabhan and Pallot 1995).…”
Section: Discussionmentioning
confidence: 99%
“…indomethacin or salicylic acid, could be used as treatments for hypoxic or ethanolinduced damage to a fetus (Randall et al 1989;Brien and Smith 1991;Espinoza and Parer 1991;Taylor et al 1994). Unfortunately, salicylic acid alone can be teratogenic (Joschko et al 1993;Padmanabhan and Pallot 1995), and together ethanol and salicylic acid compromise fetal size and viability (Guy and Sucheston 1986;Padmanabhan et al 1994;Padmanabhan and Pallot 1995). On the other hand, indomethacin does not appear to be teratogenic (Klein et al 1981), reduces mortality caused by acute overexposure to ethanol (George et al 1982), and offsets ethanol-induced alterations in cyclooxygenase activity (Knapp and Crews 1999;present study) and ischemia-induced neuronal death (e.g.…”
Section: Cox Expression and Activitymentioning
confidence: 99%
“…For the control group, 0.9% NaCl in distilled water was administered instead. The ethanol doses adopted here were in the range of published regimens with CD‐1 mice (Perez et al, 1983; Blakley and Scott, 1984; Guy and Sucheston, 1986; Epstein and Sucheston, 1987; Zidell et al, 1988; Paulson et al, 1992; Weston et al, 1994; Pastor et al, 2002), the CNS defects ratios of which were suitable for this research.…”
Section: Methodsmentioning
confidence: 99%
“…The first possible mechanism is that this highly lipophilic structure of ASA may disrupt the lipid structure of the cell membrane by increasing fluidity, as previously shown (3,38). The second possible mechanism is that ASA has an acid property, and because of this, the combined effect of aspirin and alcohol may result in lipid peroxidation (4,5). The final possible mechanism may be the disruption of synaptosomal membrane integrity by ASA because ASA has been shown to decrease the surface hydrophobicity of the mucosal membrane (16).…”
Section: Discussionmentioning
confidence: 89%
“…Aspirin may be taken with acute or chronic alcohol intake in daily life, and previous experimental studies reported that increased toxicity of salicylic acid was observed, particularly in the rodent brain (2,3). Furthermore, there are studies suggesting a synergistic effect of aspirin and alcohol (4,5). On the contrary, using a mouse model of prenatal mortality and malformation, Randal and Anton showed that aspirin has a preventive effect on prenatal mortality against the detrimental effects of alcohol (6).…”
Section: Introductionmentioning
confidence: 99%